1999
DOI: 10.1086/314775
|View full text |Cite
|
Sign up to set email alerts
|

Novel Four‐Drug Salvage Treatment Regimens after Failure of a Human Immunodeficiency Virus Type 1 Protease Inhibitor–Containing Regimen: Antiviral Activity and Correlation of Baseline Phenotypic Drug Susceptibility with Virologic Outcome

Abstract: Twenty human immunodeficiency virus-infected patients experiencing virologic failure of an indinavir- or ritonavir-containing treatment regimen were evaluated in a prospective, open-label study. Subjects received nelfinavir, saquinavir, abacavir, and either another nucleoside analog (n=10) or nevirapine (n=10). Patients treated with the nevirapine-containing regimen experienced significantly greater virologic suppression at week 24 than those not treated with nevirapine (P=.04). Baseline phenotypic drug suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
71
1

Year Published

1999
1999
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(79 citation statements)
references
References 19 publications
7
71
1
Order By: Relevance
“…Third, the signed-sum method used in the multivariate analysis of the genotypic patterns helped to simplify complex data and avoid the potential problem of colinearity between mutation predictors. Finally, recent retrospective studies support our findings, although not all of these studies have shown that the predictive capacity of resistance testing is independent of standard clinical predictors (37,(53)(54)(55)(56).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Third, the signed-sum method used in the multivariate analysis of the genotypic patterns helped to simplify complex data and avoid the potential problem of colinearity between mutation predictors. Finally, recent retrospective studies support our findings, although not all of these studies have shown that the predictive capacity of resistance testing is independent of standard clinical predictors (37,(53)(54)(55)(56).…”
Section: Discussionsupporting
confidence: 83%
“…Genotypic and phenotypic methods of measuring drug resistance are increasingly available to clinicians (31)(32)(33)(34)(35)(36)(37). However, the role of these tests in clinical practice has not been fully assessed.…”
mentioning
confidence: 99%
“…Furthermore, the cutoff value of 2.5 used for these drugs overlaps with the phenotypic interassay variability (6). However, this low value has been shown to be predictive of therapy failure (23). Nevertheless, we could obtain a concise model with good prediction results for ABC, which shows a frequency distribution of resistance factors similar to ddC, ddI, and d4T (Fig.…”
Section: And Rt Codon 75 Codes For Alanine (A) Glutamic Acid (E) Ormentioning
confidence: 95%
“…While different combination therapy regimens (which typically include reverse transcriptase [RT] and protease [PR] inhibitors) have been shown to be effective initially in reducing plasma virus loads and increasing CD4 ϩ T-cell counts, a significant percentage of individuals eventually fail therapy, as indicated by a rebound in plasma virus load (5,12,13,29,40). When effective combination therapy is used to treat subjects, the development of resistance can be delayed for years; however, when therapy is suboptimal, resistance can develop rapidly, often within weeks to a few months, and this is the typical outcome with monotherapy (reviewed in reference 38).…”
mentioning
confidence: 99%